2013
DOI: 10.1016/j.mechmat.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooperative grain boundary sliding and migration on emission of dislocations from a crack tip in nanocrystalline materials

Abstract: Interaction of the cooperative grain boundary sliding and migration with a crack in deformed nanocrystalline materials is investigated using the complex variable method. Effects of the two disclination dipoles produced by the cooperative deformation on the emission of lattice dislocations from the crack tip are theoretically described. The complex form expressions of the stress field and the force field are divided. The critical stress intensity factors for the first dislocation emission are calculated. Influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…2d). The splitting processes do not have their analogs in the previously examined [3,5,7,10,11,[18][19][20][21][22][23] situations with conventional, non-distorted GBs and lead to formation of new nanoscale (sub)-grains in nanomaterials. With these theoretical results, one can conclude that, in parallel with previously examined grain refinement mechanisms such as (i) continuous dislocation ensemble evolution resulting in sequential formation of dislocation subboundaries, cells and high-angle GBs [43][44][45], (ii) formation and intersection of elongated laminate structures and microbands [46], and (iii) re-arrangements of GB disclination structures [47,48], the stress-driven splitting of deformation-distorted GBs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2d). The splitting processes do not have their analogs in the previously examined [3,5,7,10,11,[18][19][20][21][22][23] situations with conventional, non-distorted GBs and lead to formation of new nanoscale (sub)-grains in nanomaterials. With these theoretical results, one can conclude that, in parallel with previously examined grain refinement mechanisms such as (i) continuous dislocation ensemble evolution resulting in sequential formation of dislocation subboundaries, cells and high-angle GBs [43][44][45], (ii) formation and intersection of elongated laminate structures and microbands [46], and (iii) re-arrangements of GB disclination structures [47,48], the stress-driven splitting of deformation-distorted GBs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process is new for science of stress-driven migration of GBs in nanomaterials. The splitting process has no analogs in the previously examined [3,5,7,10,11,[18][19][20][21][22][23] situations with stress-driven migration of conventional, non-distorted GBs.…”
Section: Stress-driven Migration Of Deformation-distorted Low-angle Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The brittle-ductile transition arising from the thermally activated dislocation slip can strongly influence the degradation mechanism such as fatigue, fracture and plastic deformation in high-temperature ferroelectric ceramics. Hence, the theoretical model of the process of the thermally activated dislocation slip should be first constructed by the dislocation forces (Hirth and Lothe, 1964;Feng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For nc solids with cracks, the experimental studies and theoretical derivations have found that cracks can induce plastic shear by emission of lattice dislocations from crack tips as long as the stress intensity factor of crack tips is large enough, thus hindering cracks growth and improving the toughness of nc solids. So it is very meaningful to study the effects of special rotational deformation on the emission of lattice dislocations from various crack tips [29][30][31][32][33][34][35][36][37]. Our group has theoretically investigated the effect of special rotational deformation on the lattice dislocation emission from a line crack, a semi-elliptical blunt crack tip, and an elliptical hole in nc materials and has obtained a series of important conclusions.…”
mentioning
confidence: 99%